Effectiveness of Animated Video-Based Education in Improving Diabetes Self-Management Among Patients with Type 2 Diabetes Mellitus in Pekanbaru, Indonesia - Carles Carles; Agrina Agrina; Muhammad Irwan; Eliza Fitria; Betty Nia Rulen; Agung Sutriyawan (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2026)
Background: Type 2 Diabetes Mellitus remains a major global health problem that requires effective self-management to prevent complications. Poor blood glucose management behavior, unhealthy dietary patterns, and inadequate stress management may worsen patients’ conditions. Educational interventions using audiovisual media, such as animated videos, have the potential to improve patients’ understanding and self-management behavior.Aims: This study evaluated the effectiveness of animated video-based education in improving diabetes self-management among patients with Type 2 Diabetes Mellitus in Pekanbaru, Indonesia.Methods: This study used a quasi-experimental design with intervention and control groups. A total of 200 participants were included, consisting of 100 participants in the intervention group and 100 participants in the control group. The intervention group received a 60-minute animated video-based education session, while the control group received no intervention. Data were collected before and after the intervention using questionnaires. Data were analyzed using paired t-tests, independent t-tests, and Cohen’s d.Results: The results showed significant improvements in the intervention group in blood glucose management behavior (p<0.001; Cohen’s d=2.741), dietary patterns (p<0.001; Cohen’s d=3.506), and stress management (p<0.001; Cohen’s d=3.420). Independent t-test analysis also demonstrated significant differences in score changes between the intervention and control groups across all study variables (p<0.001), with very large effect sizes.Conclusion: Animated video-based education was effective in improving blood glucose management behavior, dietary patterns, and stress management among patients with Type 2 Diabetes Mellitus.